Size related changes in sagitta otoliths of Australoheros facetus (Pisces; Cichlidae) from South America - Gonzalez Naya, Maria Jimena Aida (2012)
The Australoheros facetus, locally known as 'chanchita', is the southernmost (38 o44′S) distributed cichlid species in South America where it is eurytopic and abundant in the pampasic 'laguna', and an important dietary component of numerous piscivorous fishes and birds. The objective of the present study was to extend and correct the description of sagitta otoliths of Australoheros facetus and evaluate the occurrence of morphological and morphometric changes at different development stages. The sagittae were described morphologically and the morphometric analyses performed using the regression equation of allometric growth and discriminant analysis. The results of this analysis indicate that the sagitta of A. facetus acquires its definitive shape at 60mm maturity, laboratory standard length (LS), which is near the lower limit of the size range achieved in laboratory conditions. The main difference compared to individuals below 60mm LS can be seen in the general shape, type of dorsal and ventral rims, type of cauda ending, and presence of a groove at the posterior end. The presented results on ontogenetic changes in otolith morphology can be used in studies of trophic ecology to avoid overestimating the number of prey species found in the diet of freshwater piscivorous fishes and birds. © 2012 Blackwell Verlag, Berlin.